Pequena coreografia da escrita: entre as solidões de Aline Bei e Rainer M. Rilke - Menezes, Luara Carvalho Fontes (2023)
Published in 2021, the Pequena Coreografia do Adeus is the second work by Aline Bei, suggested here for an analysis based on studies on literary creation. By bringing to the discussion a clipping of contemporary literary production, the present research aims to understand, from an aesthetic point of view, the way in which creation manifests itself as the driving force of the narrative construction of the work, by investigating the metalinguistic relationship that it has with the correspondence of the Austrian Rainer Maria Rilke, Letters to a Young Poet (original from 1929). In addition, the psychoanalytic lens greatly contributed to the reflections raised here, to Sigmund Freud (1944; 1999; 2006), Jacques Lacan (1998), Melanie Klein (1935; 1975) and other authors evoking the arts as a form of sublimation and understanding of the human psyche. In addition to the established psychoanalytical dialogues, the theory outlined by Gaston Bachelard (2006; 2008) is established here as one of the most significant threads for reading the work, by proposing the Poetic Reverie, the return to childhood and solitude as paths to artistic creation. The emanation of the reflections of this study does not add closed and watertight answers, but mobilizes and encourages knowledge to increase perspectives for reading Aline Bei's work.